Study the reality of the knowledge management and information technology to the work of the administrative leaders in the institutions and sports bodies - Naji, Hassan; Ayad, Mohammed (Journal of Physical Education, 2015)
The study aimed to identify the level of use of knowledge management and information technology at the administrative leaders and reached the study sample (116) administrator and researcher used designer Scale by him and it includes 14 items distributed two axes (knowledge management, information technology) and have been applied on the sample mentioned and then the data processing obtained statistically and results indicated that knowledge management level and information technology to the work of the administrative leaders was high and of the most important recommendations conduct longitudinal studies regarding the level of knowledge management and information technology in all the institutions and sports bodies for the advancement of sports Iraqi